2008
DOI: 10.4314/ajhs.v13i1.30821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal mortality on gross domestic product (GDP) in the WHO African region

Abstract: SUMMARYWHO African region has got the highest maternal mortality rate compared to the other five regions. Maternal mortality is hypothesized to have significantly negative effect on the gross domestic product (GDP). The objective of the current study was to estimate the loss in GDP attributable to maternal mortality in the WHO African Region. The burden of maternal mortality on GDP was estimated using a doublelog econometric model. The analysis is based on cross-sectional data for 45 of the 46 Member States in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…This corroborates with a study that demonstrated the elimination of delays faced by community midwives/lady health visitors in providing standard healthcare services(pre-post natal) to mother and child in remote areas in Pakistan due to mobile CDSS [34].The CDSS intervention reduced complications during delivery and as a result reduced maternal deaths. Given that maternal mortality of a single mother reduced per capita GDP by US$0.36 per year in Africa [35], it is worth spending on interventions such as computer-assisted CDSS as it has the propensity of improving the management of pregnancy and delivery and as a result reduce the costs associated with managing these consequences.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates with a study that demonstrated the elimination of delays faced by community midwives/lady health visitors in providing standard healthcare services(pre-post natal) to mother and child in remote areas in Pakistan due to mobile CDSS [34].The CDSS intervention reduced complications during delivery and as a result reduced maternal deaths. Given that maternal mortality of a single mother reduced per capita GDP by US$0.36 per year in Africa [35], it is worth spending on interventions such as computer-assisted CDSS as it has the propensity of improving the management of pregnancy and delivery and as a result reduce the costs associated with managing these consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Every year, thousands of women in Haiti die from causes that could be prevented by access to comprehensive and skilled obstetric care during pregnancy, childbirth, and the postpartum period 2 , 3 . Use of maternal health services, especially facility delivery, remains low in Haiti.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the International Labour Organization's (ILO) definition of labour force includes the employed (including the armed forces), the unemployed, and the first-time job-seekers, but excludes full-time homemakers and other unpaid caregivers and workers in the informal sector. The majority of the women in Africa are either full-time homemakers and/or informal sector workers, and, thus, their invaluable contribution to society is excluded from GNI calculations [22,23]. …”
Section: Discussionmentioning
confidence: 99%